2019
DOI: 10.3390/jcm8091461
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Corticosteroids on C-Reactive Protein in Patients with Severe Community-Acquired Pneumonia and High Inflammatory Response: The Effect of Lymphopenia

Abstract: Background: Lymphopenic patients with community-acquired pneumonia (CAP) have shown high mortality rates. Corticosteroids have immunomodulatory properties and regulate cytokine storm in CAP. However, it is not known whether their modulatory effect on cytokine secretion differs in lymphopenic and non-lymphopenic patients with CAP. Therefore, we aimed to test whether the presence of lymphopenia may modify the response to corticosteroids (mainly in C reactive protein (CRP)) in patients with severe CAP and high in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
(10 reference statements)
1
7
0
Order By: Relevance
“…The most plausible explanation for the different inflammatory marker trends is the use of evidence-based immunomodulatory therapies in the second wave. Corticosteroid use has been shown to result in a reduction in CRP levels in community-acquired pneumonia [ 21 ] and IL-6 and IL-1 receptor antagonists have been also shown to drastically alter the CRP response [ 22 ]. Our finding that CRP levels were significantly reduced after the day of ICU admission, when most patients had tocilizumab, sarilumab, or anakinra administered, confirms this previous observation [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most plausible explanation for the different inflammatory marker trends is the use of evidence-based immunomodulatory therapies in the second wave. Corticosteroid use has been shown to result in a reduction in CRP levels in community-acquired pneumonia [ 21 ] and IL-6 and IL-1 receptor antagonists have been also shown to drastically alter the CRP response [ 22 ]. Our finding that CRP levels were significantly reduced after the day of ICU admission, when most patients had tocilizumab, sarilumab, or anakinra administered, confirms this previous observation [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other reports showed that the degree of CD4 T lymphopenia is higher in patients with severe COVID-19 disease than in mild cases, and is associated with disease severity [7][8][9] . The CD4 T lymphocyte count was significantly lower in elderly patients than in middle-aged and young patients, which might be related to the virus attacking the target organ at the early stage, whereas in the later period, it starts to attack the body's immune system and causes to T lymphocyte apoptosis or bone marrow suppression, which is more obvious in middle-aged and elderly patients [10][11][12] .…”
Section: Discussionmentioning
confidence: 93%
“…As a result, this difference in average CRP during these two waves may not reflect any patterns and making any conclusion about it would be factually and statistically incorrect. The role of dexamethasone administration in reducing CRP response also needs to be explored 25–27…”
Section: Discussionmentioning
confidence: 99%